Взаимодействие библиотек НИУ СО РАН для формирования и использования фондов изданий ограниченного распространения (Библиосфера)
The article describes the problems of the work with the literature of limited spread in research institutes of SB RAS. Drafts of guides for the funds with such literature are presented.